BIODIVERSITAS FAUNA MANGROVE SEBAGAI INDIKATOR KESEHATAN EKOSISTEM DI PANTAI PULAU SANTEN, BANYUWANGI - Yomi Sari Hijriyah Sari; Pradityana Putra Akbar Pratama; Latifa Mirzatika Al-Rosyid (Program Studi Teknik Lingkungan, Fakultas Teknik, Universitas Mahasaraswati Denpasar, Bali, 2026)
Mangrove ecosystems play an important role in maintaining ecological balance and supporting the socio-economic life of communities. This study aims to identify the biodiversity of mangrove fauna and its role as a bioindicator of ecosystem health on the coast of Santen Island, Banyuwangi, using a descriptive qualitative approach through field observations, interviews, and documentation. The results of the study show that there are six main types of fauna found at the study site, namely mangrove crabs, Cere fish, Tembakul fish, shrimp, kijing shellfish, and brackish water crabs, as well as a mangrove ecosystem dominated by the Rhizophora mucronata species. The presence of these fauna indicates that the condition of the mangrove ecosystem is still relatively healthy. Environmental factors such as mud thickness, salinity levels, and mangrove vegetation density have a significant effect on fauna diversity. In addition, human activities such as tourism and domestic waste disposal have the potential to reduce the quality of the ecosystem. Overall, the results of this study confirm that mangrove fauna can be used as effective bioindicators to assess the ecological conditions of coastal areas. Therefore, community-based conservation efforts and the application of sustainable ecotourism concepts are needed to maintain ecological, economic, and social balance in the coastal area of Santen Island, Banyuwangi.